Managing Static Archives for Historical Research: A Study at the Archives Depot of the East Java Provincial Library and Archives Service, Indonesia - Mustakim, Farah Mumtahanah; Adi Prasetyawan (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study investigated the procedures for managing static archives as historical research sources and the challenges encountered in the management process at the the Archives Depot of the East Java Provincial Library and Archives Service, Indonesia. Data were collected through observations, semi-structured interviews, and documentation. The study applied static archive management theories, encompassing record selection, accessioning, arrangement, description, conservation, preservation, storage, and reference functions. The findings revealed that static archive management involves interconnected processes, including selecting records, accessioning, arranging, describing, preserving, and utilizing archives for historical research. Despite the structured procedures, internal challenges such as limited archivist competence, insufficient technical and operational support, and inadequate budgets, facilities, and infrastructure hinder optimal management. External challenges stem from the low public awareness of the importance of preserving static archives. It underscores the universal importance of effective static archive management in preserving historical records for future generations. It highlights common challenges faced by archival institutions, particularly in resource-constrained environments, and offers insights that can inform best practices globally.